2010
DOI: 10.1007/s00359-010-0576-7
|View full text |Cite
|
Sign up to set email alerts
|

A pair of motion-sensitive neurons in the locust encode approaches of a looming object

Abstract: Neurons in the locust visual system encode approaches of looming stimuli and are implicated in production of escape behaviours. The lobula giant movement detector (LGMD) and its postsynaptic partner, the descending contralateral movement detector (DCMD) compute characteristics of expanding edges across the locust eye during a loom and DCMD synapses onto motor elements associated with behaviour. We identified another descending interneuron within the locust ventral nerve cord. We named this neuron the late DCMD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 55 publications
3
39
1
Order By: Relevance
“…Based on the equation of the linear regression line (Fig.10) we can predict changes in FWA and η angle using DA. This prediction will be used in computer-generated closed-loop experiments to provide appropriate visual feedback during flight steering while recording from suites of flight muscles and multiple motion-sensitive visual neurons (Gray et al, 2010), allowing for an unprecedented understanding of the neural mechanisms of adaptive behaviour in this model system. (r=0.42, y=0.97x-5.72), DA and η (r=0.46,y=0.73x+1.36),and FWA and η (r=0.55,).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the equation of the linear regression line (Fig.10) we can predict changes in FWA and η angle using DA. This prediction will be used in computer-generated closed-loop experiments to provide appropriate visual feedback during flight steering while recording from suites of flight muscles and multiple motion-sensitive visual neurons (Gray et al, 2010), allowing for an unprecedented understanding of the neural mechanisms of adaptive behaviour in this model system. (r=0.42, y=0.97x-5.72), DA and η (r=0.46,y=0.73x+1.36),and FWA and η (r=0.55,).…”
Section: Discussionmentioning
confidence: 99%
“…It also plays a role in triggering jumps (Fotowat and Gabbiani, 2007;Santer et al, 2008), and recent evidence suggests that it plays distinct roles during different phases in preparing for and performing a jump (Fotowat et al, 2011). The DCMD acts in concert with other interneurons in the control of jumps, some of which respond to approaching stimuli (Gray et al, 2010;Simmons and Rind, 1997). The natural predators that chase locusts might differ according to the age and size of locusts, as has been shown for Nemobius crickets, in which early instars are particularly vulnerable to predation by wolf spiders (Dangles et al, 2007).…”
Section: The Journal Of Experimental Biology 216 (12)mentioning
confidence: 99%
“…Investigations in the locust highlighted the role of the LGMD in the avoidance responses to looming stimuli, but also showed that other LSNs, such as the LGMD2 (Rind, 1996), are likely involved with the execution of those responses (see also Gray et al, 2010;Sztarker and Rind, 2014). While escaping from an approaching object, crabs continuously regulate their speed (Oliva and Tomsic, 2012) and direction of run (Medan et al, 2015).…”
Section: Different Lsns Working Togethermentioning
confidence: 99%
“…Such neurons are commonly referred as looming sensitive neurons (LSNs). LSNs have been found in pigeons (Wang and Frost, 1992), fish (Preuss et al, 2006), monkeys (Maier et al, 2004) and different arthropod species such as locusts (Rind and Simmons, 1992;Gabbiani et al, 1999;Gray et al, 2010), flies (Borst, 1991;Fotowat et al, 2009), crayfish (Glantz, 1974) and crabs Oliva and Tomsic, 2014). But, how is the visual information of an approaching object actually processed, encoded and conveyed by LSNs to contribute to avoidance behaviors?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation